Control and Calculation of Industrial Machine Effectiveness Based on Programmable Logic Controller and Human Machine Interface - Maryanto, Adika; Yuliantari, Risky Via; Fatkhurrozi, Bagus (Journal of Energy and Electrical Engineering, 2024)
In today's fast growing technology, industries need a system that is able to control machines more effectively and efficiently to improve quality and reduce production costs. In addition, an efficient control system can minimize excessive process time. PT Chemco Harapan Nusantara, a manufacturing company, requires a system to automate the control of the Vibratory Deburring Machine or barrel machine which is currently still operated manually. This manual operation increases the production process time. This research aims to develop an automation system for controlling and evaluating the effectiveness of industrial machines using a Programmable Logic Controller and Human Machine Interface to increase production efficiency and reduce processing time. Testing in this study was carried out by simulating the production process at PT Chemco Harapan Nusantara 28 times. The results showed that the highest percentage of effectiveness obtained was 99.94% with a loss time of 14 seconds, while the lowest percentage was 99.91% with a loss time of 23 seconds. The average effectiveness reached 99.96% with a loss time of 9 seconds. In addition, the process time was successfully reduced by 20 seconds from over 5 minutes 20 seconds to only 5 minutes.